Pengendalian Persediaan Obat Generik Bermerek Menggunakan Metode Analisis ABC, Economic Order Quantity (EOQ), dan Reorder Point (ROP) di Instalasi Farmasi RS “X” Tahun 2022: Inventory Control of Branded Generic Drug Using ABC Analisys Method, Economic Order Quantity (EOQ), and Reorder Point (ROP) at Pharmaceutical Installation of RS “X” 2022 - Ditha Anastasia; Ervianingsih Ervianingsih; Izal Zahran (Jurnal Surya Medika (JSM), 2023)
Inventory control is a very important element in the management of pharmaceutical supplies. Inventory control at Hospital “X” in Palopo City is currently using the consumption method, which has the risk of running out of medicine (stock out). Methods that can minimize this risk are the ABC, EOQ, and ROP analysis methods. The research aims to group drug items into 3 ABC groups based on investment value, find out the optimal order quantity using the economic order quantity (EOQ) calculation, and determine the time to reorder drugs using the reorder point (ROP) calculation. This type of research is non-experimental and uses mixed methods; data collection is done retrospectively for quantitative data and directly for qualitative data. The results of the analysis of the ABC method of branded generic drug included in group A were 18 types (12%) with an investment value of 70.17% of the total investment value, group B, namely 22 types (14.67%) with an investment value of 20.38 % of the total investment value, and group C drugs, namely 110 types (73.33%) with an investment value of 9.46% of the total investment value. Based on the EOQ calculation analysis, the optimal number of orders for group A branded generic drugs varied between 683 and 34 units. The results of the calculation and analysis using the ROP method show that the reorder point for group A branded generic drugs varies between 234 and 7 for each drug unit.